The Use of Foreign Exchange Swaps by Central Banks : A Survey - Hooyman, Catharina (IMF Working Papers; Working Paper ;, 1993)
The paper discussed the use of foreign exchange swaps by central banks. Such use has aimed at affecting domestic liquidity, managing foreign exchange reserves, and stimulating domestic financial markets. It discusses these different uses and present evidence for a selected group of countries. The paper cautions about the use of foreign exchange swaps to defend a particular exchange rate at a time when foreign exchange reserves are under pressure. It notes, finally, that use of foreign exchange swaps by central banks has been losing importance.